MUSCULAR ARTERIAL TONE IS A DETERMINANT OF PERIPHERAL MUSCULAR ARTERY STIFFNESS. (June 2018) - Patzak, A.; Braun, D.; Schleifenbaum, J.; Küchler, G.
Abstract : Objective: Due the practical weaknesses of cuff based methods for arterial blood pressure (BP) measurement, efforts are made to establish non-invasive and continuous PB measurement by using alternative methods. One of them is based on the determination of the pulse transit time and pulse wave velocity (PWV), respectively. Arterial BP and PWV correlate, which opens the possibility of the determination of arterial BP by measuring the pulse transit time (PTT). Recent validation studies revealed usefulness of this method in clinical practice. The accuracy of this method depends on the transfer function (model) between arterial BP and PWV. Since PWV is mainly determined by the arterial elasticity (stiffness), knowledge about the contribution of different components and to the arterial stiffness as well as their modulation is important. We hypothesize that the vascular smooth muscle (VSM) tone significantly determines arterial stiffness in muscular arteries and thus may contribute to the PWV-BP relation. Design and method: We used the pressurized artery method and investigated the influence of inherent and pharmacologically modified VSM tone on measures of arterial stiffness. We first characterized passive and active components of arterial stiffness by calculating pressure-diameter-relation, stress-strain-relation, and the stiffness parameter beta in vessels with spontaneous tone and in vessel after calcium depletion. Further, the effect of norepinephrine in different concentrations on the measures of stiffness was investigated. Results: Vessels with spontaneous myogenic tone showed left shifted pressure-diameter- and stress-strain-relations compared to passive vessels, expressing an increased vascular stiffness. Norepinephrine in higher concentration further shifted these curves to the left and consequently increased vessel stiffness. The stiffness parameter beta was also increased. Conclusions: The data suggest that the myogenic tone and the action of norepinephrine increases arterial stiffness in muscular arteries of rats. This effect may contribute the PWV in muscular arterioles and thus influences to the PWV-BP relation.